2014
DOI: 10.1177/1052562914521197
|View full text |Cite
|
Sign up to set email alerts
|

How Network Properties Affect One’s Ability to Obtain Benefits

Abstract: Networks and the social capital that they carry enable people to get things done, to prosper in their careers, and to feel supported. To develop an effective network, one needs to know more than how to make connections with strangers at a reception; understanding the consequences of network properties on one's ability to obtain benefits is essential. Such understanding enables students to better assess who to connect to. The simulation described herein enables participants to experience and therefore better un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…However, it also seems that of the three career capitals, knowing whom developed the most during their IA (mean 5.5). This finding may be interpreted in the light of the current understanding of the strength and importance of network properties, beyond just the number of the contacts one has (Trefalt, ). As the structure of the expatriate's network is likely to change during their assignment, it is possible that, despite the increase in the level of their knowing whom career capital, structurally their network is not optimal in terms of marketability: on the one hand, ties in the home organization are likely to weaken, and on the other hand, recently created new ties are not strong enough to provide access to information channels important for marketability.…”
Section: Discussionmentioning
confidence: 71%
“…However, it also seems that of the three career capitals, knowing whom developed the most during their IA (mean 5.5). This finding may be interpreted in the light of the current understanding of the strength and importance of network properties, beyond just the number of the contacts one has (Trefalt, ). As the structure of the expatriate's network is likely to change during their assignment, it is possible that, despite the increase in the level of their knowing whom career capital, structurally their network is not optimal in terms of marketability: on the one hand, ties in the home organization are likely to weaken, and on the other hand, recently created new ties are not strong enough to provide access to information channels important for marketability.…”
Section: Discussionmentioning
confidence: 71%
“…This suggests that one way of building relationships with students is by being committed to them and showing that you care. Our review of the literature yielded several articles that provide instructional ideas for building students' network of personal and professional relationships that we encourage professors to consider (e.g., Gerard, 2012;Trefalt, 2014). Second, because knowing oneself is essential to identity formation for emerging adults, when identifying activities for management students, instructors should ask, Does the activity present the emerging adult learners with opportunities for self-reflection?…”
Section: Self-concept Of the Emerging Adult Learnermentioning
confidence: 99%
“…Several studies had suggested that people are typically reluctant to engage in networking efforts (Bensaou et al, 2014;de Janasz & Forret, 2008;Ferrazzi, 2005;Ibarra, 2016;Ibarra et al, 2010;Kuwabara et al, 2018;Trefalt, 2014;Wanberg et al, 2000). The strength of CGK was to provide a psychological mechanism explaining this reluctance, and to offer causal empirical evidence for this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The idea that people feel uncomfortable networking predates CGK: Multiple studies have described what people feel or think about networking. A general conclusion is that people hold negative views of networking activities: People often describe networking as "uncomfortable," "awkward," "humiliating," "threatening," "intimidating," "unfair," "inappropriate," "illegitimate," "presumptuous," "unnatural," "insincere," "dishonest," "fake," "artificial," "manipulative," "selfish", "useless" or "immoral" (Bensaou et al, 2014;de Janasz & Forret, 2008;Ferrazzi, 2005;Ibarra, 2016;Ibarra, Carter, & Silva, 2010;Kuwabara et al, 2018;Trefalt, 2014;Wanberg, Kanfer, & Banas, 2000). However, not only those papers are purely descriptive (i.e., theoretical, qualitative, or correlational), but they also do not explore the mechanism that leads to discomfort and the specific negative psychological state networking triggers.…”
Section: Theorymentioning
confidence: 99%